NHS commissioning in probation in England – on a wing and a prayer. (1st October 2015) - Brooker, Charlie; Sirdifield, Coral; Ramsbotham, Lord David; Denney, David
Abstract: National guidance in England exhorts Clinical Commissioning Groups [groups of general practices established to organise delivery of National Health Service (NHS) care in their local area (CCGs)] to commission healthcare for those living in the community who are serving non‐custodial sentences called 'community orders'. This includes 'approved premises' – accommodation providing enhanced supervision for offenders and individuals on bail who may present a high risk of harm to the public. In this national survey of CCGs in England, we compared the extent to which healthcare services were commissioned for probationers in 2014 with similar data we collected in 2013. A freedom of information (FOI) request was sent to all CCGs ( n = 212) and Mental Health Trusts (organisations commissioned to provide health and social care services to individuals with mental health disorders) ( n = 53) in England. Mental Health Trusts were included as they were known to fund mental health services for probation as part of their block funding allocations. A small number of basic questions were asked. The response rate was good with 65% of CCGs ( n = 137) and 68% ( n = 36) of Mental Health Trusts responding. The findings show that the proportion of CCGs commissioning healthcare for probation reduced from 7% to 1%, with 20% of CCGs stating that funding healthcare for this group was the responsibility of the NHS England Area Teams. There was also a reduction in the proportion of Mental Health Trusts funding healthcare for probation but from a much higher baseline, that is from 70% to 61%. The prevalence of mental health disorders in probation is high, so it was of concern that only 12% of Mental Health Trusts provided a service to support approved premises and just 32% provided clinics in probation. The results are discussed within the context of the NHS reforms and the government's plans in England to reform probation.